The Implementation of True and False Game in Studi Independen Program at English Village - Habibi, Wahyu; Sahrawi; Hafis, Maliqul; Meliasari, Rahayu; Susanti, Heti (IKIP PGRI Pontianak, 2024)
True and false is the implementation of game that can be played in groups or individually which is students answer questions by answering True or False. This research aimed to determine the implementation of true and false game in English Village of Parit Baru and the effects of implementation true and false game in studi independen at English Village of Parit Baru. This research used a descriptive qualitative approach. The researcher used a interviews, questionnaire, observation and document as tools of data collection. The subject of this research was student at English Village of Parit Baru. The researcher used data reduction, data display and draw a conclusion to analyze the data. The results of this research showed that the implementation true and false game was successfully regarded. Although it has only been applied a few times and we don’t know the result of students learning outcomes accurately but we know that students are have fun, enjoy learning and increase students enthusiasm. This research has the potential to be further developed as a classroom action research.